Hermann Dörries: ein Kirchenhistoriker im Wandel der Zeiten - Dornbusch, Aneke; Gemeinhardt, Peter (Arbeiten zur Kirchengeschichte, 2023)
As a church historian, Hermann Dörries (1895–1977) taught and researched in various political contexts. This volume examines how these upheavals are reflected in his works and how Dörries used his historical research to interpret contemporary events. Biographical and thematic studies paint a differentiated picture of this influential scholar against the backdrop of twentieth-century German history